(untitled) (Impetus, 2021)
The aim of this study was to establish reflections on the recent wave of violence that occurred in Brazilian football, or more specifically, in the context of fans. Therefore, we set out to reflect on the events of a few games of football and its impact on the national and international media as the match between Atletico Paranaense and Vasco da Gama, in Joinville, in 20013. This event determined to Vasco relegation to the second division of Brazilian football. It is important to mention that the episode caused a series of interventions by the prosecutor, and the legal conflict betweenthese clubs and the entity that controls the national football, the Brazilian Football Confederation (CBF). The game was stopped and restarted after many discussions - extra field - involving the leaders of the CBF. This fact contradicted many people who have not found more atmosphere to the game. At this point, among other concepts of Elias (1992), we can say that the aspect “liberating excitement,” strongly highlighted by the German sociologist, that sports can provide, was completely unaffected, since the leaders had no sensitivity to the events, as well as the general climate that led to this barbarism.